1968
DOI: 10.1107/s0567740868001937
|View full text |Cite
|
Sign up to set email alerts
|

Atomic ordering in binary Al5-type phases

Abstract: The degree of long-range order has been determined for 20 binary A 15-type phases containing various transition elements. A tendency toward a lower degree of order was noted as the component elements were chosen successively from columns in the periodic table approaching the Mn column. A comparison of the ordering in the A 15-type phases with the ordering previously reported for various binary a phases suggests that the remarkable stability of these phases may result from an interdependence between the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
20
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(26 citation statements)
references
References 8 publications
6
20
0
Order By: Relevance
“…A more recent investigation of Cr72Ru28 and Cr12Os28 alloys with A 15 type structure and compositions deviating from stoichiometry has shown that the occupancies of sites lying along linear chains are mixed (Reuth & Waterstrat, 1968). The Cr atoms, however, show in both cases a marked preference for those sites (~85 at.% Cr); the same marked preference is evidenced by the present results for a-Cr2Ru and tT-Cr2Os.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A more recent investigation of Cr72Ru28 and Cr12Os28 alloys with A 15 type structure and compositions deviating from stoichiometry has shown that the occupancies of sites lying along linear chains are mixed (Reuth & Waterstrat, 1968). The Cr atoms, however, show in both cases a marked preference for those sites (~85 at.% Cr); the same marked preference is evidenced by the present results for a-Cr2Ru and tT-Cr2Os.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, binary alloys possessing the A 15 type of structure might be expected to be completely ordered, the occupancies of the A and B atomic sites being dictated by a definite stoichiometric composition A 3 B. This has been observed in a number of cases; however, some degree of disorder has been found in some phases (Reuth & Waterstrat, 1968;Waterstrat & Dickens, 1974).…”
Section: Discussionmentioning
confidence: 95%
“…This is in agreement with results obtained for other Cr alloys with group-8 diluents that also show SC, such as in the case of Cr-Ir, Cr-Ru and Cr-Rh [1,5,10]. However, Cr alloys with high diluent concentrations of group-8 metal does not exclusively show a body centered cubic (bcc) structure, but also include binary phases such as Cr 3 X with a cubic A15 phase, shown to be SC [11][12][13][14]. * corresponding author; e-mail: alettap@uj.ac.za…”
Section: Introductionsupporting
confidence: 80%
“…Any structure in the library can be predicted and there are no preconceived biases as to the symmetry or underlying superlattice of the structure as is the case for methods that work with lattice model approaches. For example, in the Ti-Pt alloy, our method correctly finds the A15 [18,19] structure to be a ground state for Ti 3 Pt after only 20 steps in the algorithm, even though this structure is not a superstructure of fcc (the structure of Pt) or hcp (the structure of Ti), and is therefore not an obvious structure to investigate for this system. To study in a more statistically significant way how this iterative scheme converges we tested how well the library minus one alloy can perform predictions on the alloy left out.…”
mentioning
confidence: 99%